Investigation of clonal relationships of K. pneumoniae isolates from neonatal intensive care units by PFGE and rep-PCR - Mehmet Koroglu; Ahmet Ozbek; Tayfur Demiray; Taner Hafizoglu; Ertugrul Guclu; Mustafa Altindis; Oguz Karabay; Riza Durmaz (Journal of Infection in Developing Countries)
Introduction: Clonal relationships of Klebsiella pneumoniae strains obtained during an epidemic and after a one-year post-epidemic (non-epidemic) period in the same neonatal intensive care unit (NICU) using pulsed-field gel electrophoresis (PFGE) and repetitive polymerase chain reaction (rep-PCR) by the DiversiLab (DL) system were investigated, and the results of both molecular techniques were evaluated. Methodology: Fifteen K. pneumoniae strains were included in this study. All identified bacterial strains were confirmed by 16S rDNA sequencing and analyzed by PFGE and the DL system. Results: According to the PFGE results, 15 isolates showed 10 different band profiles. Nine of these 15 isolates were included in one of the formed clusters, and the remaining six isolates were not included in any of them. According to the DL system results, 15 isolates showed two different clusters, with three strains in one cluster and four strains in the other. The remaining strains could not be placed any one of the clusters. PFGE was used as the gold standard based on its strong genetic discriminatory power. The DL system results showed that  PFGE missed the relationship of the two epidemic-related strains and demonstrated one epidemic-unrelated strain to be epidemic related. Conclusions: Both systems may easily be used for clonal relationships of K. pneumoniae strains. The DL system was clearly more rapid and convenient than PFGE, but its discriminatory power seemed to be inferior to that of PFGE based on 15 K. pneumoniae strains.